RIGHTEOUS WOMEN AND SUBMISSION: Between Islamic Texts and Muslim Women’s Perspectives - Izza, Farah Nuril; Jamilah, Jamilah; Sa'diyah, Zaimatus (Ulul Albab: Jurnal Studi Islam, 2025)
This article explores the contested concepts of righteous women and submission in Islamic literature, and how Muslim women perceive, interpret, and embody these ideals in daily life. Combining textual analysis with field research, this study investigates women's agency within Islamic frameworks, particularly how religious texts are internalized, contested, or reinterpreted. Primary sources include classical and contemporary tafsir and hadith literature, alongside key works on gender and women’s agency in Islam. Additionally, semi-structured interviews were conducted with ten Muslim women from diverse educational and socio-cultural backgrounds to capture a range of lived experiences. The findings reveal that classical to modern mufassirun predominantly associate women's righteousness with obedience, primarily to God and to husbands, especially in the marriage context. In contrast, contemporary scholarship increasingly frames righteousness as a personal moral and ethical responsibility beyond marital obedience. The interviews reflect this interpretive variation: while some Muslim women uphold traditional views, others prioritize intellectual autonomy, spiritual depth, and egalitarian relationships in the household. The study also identifies varied expressions of women's agency, including devotional commitment, subtle resistance, and strategic engagement with religious norms. Amid ongoing debates over gender roles in Islam, this article underscores the need for a nuanced understanding of how Muslim women actively negotiate religious texts within evolving socio-cultural contexts. It contributes to broader discourses on Islamic feminism, gender justice, and interpretive authority. It also offers fresh insights into the dynamic interface between scripture, tradition, and lived female piety.